Application of e-commerce amongst small medium enterprises: a case study in Kelantan / Norudin Mansor, Che Ismail Long and Ahmad Ismail Mohd Anuar - Mansor, Norudin; Long, Che Ismail; Mohd Anuar, Ahmad Ismail (2008)
This study was designed to investigate and broadening the understanding of e-commerce focusing on its application among the Bumiputera SMEs in the state of Kelantan. The study was descriptive in nature and cross-sectionally investigated based on the population generated by Dewan Pemiagaan Melayu Kelantan. A total of 3 02 _ respondents were selected to participate in our study. With the assumption that e-commerce application is all about acquiring knowledge and understanding the environment, coping with changes, and speeding up the business decision, thus the need to promote its usefulness in achieving the competitive advantage could be enhanced. For the purpose of addressing the issues of the research questions, 5 independent variables were explored and tested to demonstrate its usefulness towards motivating SMEs to adopt e-commerce. The result of the study indicated that there were significant relationships between logistic, marketing, procurement, security, and government; and the application of e- commerce among the SMEs establishment in the state of Kelantan. The result of the study displayed that there were significance differences between the types of business establishment, profile of education levels, and the application of e-commerce. Our attempt to denote the strength of the predictors with the r-square value of 73.2 %, provides indicators of their importance towards enhancing the application of e-commerce and thus maintaining competitive advantage in the industry. Although the selected variables indicated the significant relationship, more attempts should be done by the SMEs as well as the authorities to address the issue of security that becomes the greatest concerned for the development of e-commerce.